A call to arms: Setting the framework for a code of practice for mosquito management in European wetlands. Issue 6 (5th May 2020) - Martinou, Angeliki F.; Schäfer, Stephanie M.; Bueno Mari, Rubén; Angelidou, Ioanna; Erguler, Kamil; Fawcett, James; Ferraguti, Martina; Foussadier, Rémi; Gkotsi, Trisevgeni V.; Martinos, Christos F.; Schäfer, Martina; Schaffner, Francis; et al.
Abstract: Wetlands provide multiple services to human societies. Despite policies dedicated to their protection, current European policies do not address the need to balance mosquito management approaches to mitigate dis‐services to human health and well‐being while ensuring that wetland conservation goals are met. Herein, we outline criteria for consideration when developing mosquito control programmes in European wetlands that will allow managers and public health authorities to adopt effective and ecologically sound approaches. Synthesis and applications . The proposed code of practice provides practical advice to local authorities and those involved in mosquito control in order to design an integrated mosquito management strategy that aligns with current environmental legislation. Although this code of practice was developed by European experts, it is transferable to other geographical contexts, integrating the expertise and knowledge of local stakeholders and researchers from the fields of medical entomology, human and animal health and ecology. Abstract : The proposed code of practice provides practical advice to local authorities and those involved in mosquito control in order to design an integrated mosquito management strategy that aligns with current environmental legislation. Although this code of practice was developed by European experts, it is transferable to other geographical contexts, integrating the expertise and knowledge of local stakeholders and researchers from the fields of medical entomology, human and animal health and ecology. Περίληψη: Οι υδροβιότοποι προσφέρουν σημαντικά αγαθά και υπηρεσίες στις ανθρώπινες κοινωνίες. Η προστασία τους βασίζεται σε διεθνείς συνθήκες και νομοθεσίες. Η σύγχρονη Ευρωπαϊκή πολιτική παρά ταύτα δεν εξετάζει αν η προσέγγιση κατά τη διάρκεια προγραμμάτων ολοκληρωμένης διαχείρισης κουνουπιών στοχεύει τόσο στο να μην προκύψουν αρνητικές επιπτώσεις στην ανθρώπινη υγεία και την ευημερία, όσο και στη διατήρηση της βιοποικιλότητας των υδροβιότοπων. Στην παρούσα μελέτη περιγράφονται τα κριτήρια που θεωρούνται απαραίτητα κατά τη διάρκεια του σχεδιασμού και της εφαρμογής προγραμμάτων ολοκληρωμένης διαχείρισης κουνουπιών σε υδροβιότοπους της Ευρώπης. Τα κριτήρια αυτά έχουν ως στόχο να βοηθήσουν τόσο τους φορείς προστασίας των υδροβιότοπων όσο και τους υπεύθυνους προγραμμάτων διαχείρισης κουνουπιών ώστε να υιοθετήσουν και να εφαρμόσουν πρακτικές φιλικές προς το περιβάλλον. Σύνθεση και εφαρμογές: O κώδικας πρακτικής παραθέτει πρακτικές συμβουλές σε όσους έχουν σχέση με την ολοκληρωμένη διαχείριση κουνουπιών ώστε να μπορούν να σχεδιάσουν μία στρατηγική εναρμονισμένη με τη σύγχρονη περιβαλλοντική νομοθεσία. Παρόλο που ο κώδικας πρακτικής που παρουσιάζουμε συντάχθηκε από Ευρωπαίους ερευνητές μπορεί να μεταφερθεί και σε άλλες γεωγραφικές περιοχές ενσωματώνοντας τις γνώσεις και την εμπειρία τοπικών φορέων κι εμπειρογνωμόνων από τους τομείς της εντομολογίας, της ανθρώπινης υγείας, της κτηνιατρικής και της οικολογίας.